PENILAIAN PENGUNJUNG TERHADAP FASILITAS OBJEK WISATA DANAU CIPOGAS KABUPATEN ROKAN HULU - Aqmarina, Fildzah Atika; ", Musadad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Facilitity is a component which can support the course of activities in a tourist destination. This study was conducted at Cipogas Lake Tourist Attraction which is located in the village of Sialang Jaya and Rambah Tengah Barat, District of Rokan Hulu. Cipogas Lake Tourist Attraction is a dam which has large rocks with a river flow from the foot of haorpit hill which is steep and rocky. Cipogas Lake as one of the tourist objects which has quite complete facilities, therefore it is necessary to assess the existing facilities in Cipogas Lake to determine visitior satisfaction and increase tourist visits. The goal of this study is to determine how the visitor’s assessment of the facilities of the Cipogas Lake Tourist Attraction in the District of Rokan Hulu. This study uses a quantitative descriptive method to explain the problems raised. As for the sample, it was 99 people who were taken using accidental sampling method. While the data collection techniques in this study are observation, questionnaires, and documentation using a Likers Scale as a measuring tool. Based on the results of this study, the facilities for the Cipogas Lake Tourist Attraction in the District of Rokan Hulu is in the fairly good category.Keywords : Tourism, Facility, Visitor, Tourist Attraction.